Evaluation of oleiferous brassicas, staggered sowing and fertility level for improvement in potato (Solanum tubersosum)-based intercropping systems - RANA, D S; SARAN, GANGA; SINGH, RANBIR; RANA, K S (The Indian Journal of Agricultural Sciences, 2014)
In a field experiment conducted during the winter (rabi) seasons of 1995-97 at New Delhi, Indian mustard [Brassica juncea (L.) Czernj. & Cosson], karan rai (Brassica carinata A. Braun) and goblzi sarson [Brassica napus L. ssp oleifera DC. var annua] were evaluated as intercrop with potato (Solanum tuberosum L.) in 3 : 1 replacement series (3 rows of potato + 1 row of Brassica spp) under staggered sowing (sowing of Brassica spp at the time of potato planting and 20 days after potalo planting) and fertility levels (No, N 75, N 150’ N7S + S30 and N150 + S30) Intercropped potato received variable quantum of solar radiation at 70 and 90 days after planting of potato owing to differences in intercrop-canopy formation, maximum being in association with karan rai (90.3-98.7%). Sole stand of each crop gave significantly higher yield than their respective intercropped stand but the tuber (22.8 tonnes/hu, 81.4%) and seed yields (1.62 tonnes/ha, 60.3%) recovery in intercropped stand in relation to sole stand was the highest in potato + B. carinata system. This system also showed its signiticant superiority to other sysrems (or tuber equivalent (35.90 tonnes/ha), protein (0.75 tonne/ha) and oil (0.65 tonne/ha) yields, land-equivalent ratio (i.42), energy output (122 500 MJ), energy-lise efficiency (4.23), net return (Rs 15 800/ha) and net return/rupee investment (0.78). Staggered sowing improved the productivity of potato, but this increase was not enough to compensate for disadvantage to brassicas under uelayed sowing. Values of competition function revealed dominance of Brassica improver potato. Tuber yield (15.5-26.9 tonnes/ha), tuber equivalent (20.8-35.8 tonnes/ha), prolein (0.36-0.78 tonne/ha) and oil yields (0.31-0.48 tonne/ha) and energy (52 500-97 400 MJ/ha) nnd economic parameters recorded perceptible increase with successive increase in N level up to 150 kg N/ha. Application of N+S caused marked increase in tne productivity and net return/rupee investment over the N alone.